2020
DOI: 10.1002/cphc.201901171
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring a Zinc Oxide Nanorod Surface by Adding an Earth‐Abundant Cocatalyst for Induced Sunlight Water Oxidation

Abstract: Herein, a detailed investigation of the surface modification of a zinc oxide (ZnO) nanorod electrode with FeOOH nanoparticles dispersed in glycine was conducted to improve the water oxidation reaction assisted by sunlight. The results were systematically analysed in terms of the general parameters (light absorption, charge separation, and surface for catalysis) that govern the photocurrent density response of metal oxide as photoanode in a photoelectrochemical (PEC) cell. ZnO electrodes surface were modified w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
3
1
0
Order By: Relevance
“…SEM images of ZnONRs show that the rods have a hexagonal shape with an average diameter of 490 nm, as shown in Figures F and A. The results are consistent with studies previously published by the group , and other researchers. After SARS-CoV-2 recombinant spike protein immobilization, visual morphological changes were observed. The surface of the nanorods does not look smooth; it seems to be covered, indicating that an optimal immobilized protein profile was achieved (Figure B).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…SEM images of ZnONRs show that the rods have a hexagonal shape with an average diameter of 490 nm, as shown in Figures F and A. The results are consistent with studies previously published by the group , and other researchers. After SARS-CoV-2 recombinant spike protein immobilization, visual morphological changes were observed. The surface of the nanorods does not look smooth; it seems to be covered, indicating that an optimal immobilized protein profile was achieved (Figure B).…”
Section: Resultssupporting
confidence: 90%
“…SEM images of ZnONRs show that the rods have a hexagonal shape with an average diameter of 490 nm, as shown in Figures 2F and 3A. The results are consistent with studies previously published by the group 61,79 and other researchers. 80−82 After SARS-CoV-2 recombinant spike protein immobilization, visual morphological changes were observed.…”
supporting
confidence: 92%
“…The SEM images in Figure 3 A,B demonstrate that ZnONRs are highly dense and grown on the surface of FTO glass substrates. The high-magnification SEM image in Figure 3 C reveals that the ZnONRs obtained possess a hexagonal morphology, with an average diameter of approximately 200–300 nm, consistent with results reported elsewhere [ 16 , 22 , 29 ]. SEM images of the FTO-ZnONRs/spike WT and the FTO-ZnONRs/spike P.1 electrodes are presented in Figure 3 D,E, respectively.…”
Section: Resultssupporting
confidence: 89%
“…Glycine was used as an agent to prevent non-specific antibody binding on the device surface and to have a low dielectric constant [ 18 , 19 , 20 , 21 ]. In previous work, we have demonstrated that the glycine coating works directly on the ZnO nanorods since it has a good affinity for carboxylic groups [ 22 ]. A volume of 20 μL of serum sample diluted 1:500 ( v / v ) in PBS (pH 7.4) was incubated for 1 h on the electrode surface, rinsed to wash away the unbound material (non-specific antibodies), and subsequently dried.…”
Section: Methodsmentioning
confidence: 99%